1981
DOI: 10.1007/bf01400969
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation and fibrinolysis in blood and cerebrospinal fluid after aneurysmal subarachnoid haemorrhage: Effect of tranexamic acid (AMCA)

Abstract: Serial assays of blood coagulation factors as well as of fibrin/fibrinogen degradation products (FDP) and plasminogen activatory activity (PA) on fibrin plates in blood and cerebrospinal fluid (CSF) were performed in 41 consecutive patients with recently ruptured cerebral aneurysms, 21 of whom were randomly treated with tranexamic acid (AMCA). Coagulation factors were unaffected by the drug and plasminogen and FDP decreased in blood after two weeks' treatment. After one week, PA in CSF was increased in control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
1

Year Published

1982
1982
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 49 publications
1
20
1
Order By: Relevance
“…1 In the past, several studies investigating plasma fibrinolytic activity in patients with SAH did not demonstrate an increase in plasma fibrinolytic activity. [2][3][4] However, in contrast to the results of these older studies, we observed in our study an unexplained 3-week increase in plasma fibrinolytic activity in placebo-treated patients.…”
contrasting
confidence: 56%
“…1 In the past, several studies investigating plasma fibrinolytic activity in patients with SAH did not demonstrate an increase in plasma fibrinolytic activity. [2][3][4] However, in contrast to the results of these older studies, we observed in our study an unexplained 3-week increase in plasma fibrinolytic activity in placebo-treated patients.…”
contrasting
confidence: 56%
“…There is increased local fibrinolytic activity in cerebrospinal fluid (CSF) after aSAH [24,31,32,[34][35][36]. It has been suggested that determination of CSF FDP levels may be beneficial in establishing baseline as well as post-dose CSF fibrinolytic activity, and allow drug regimens to be tailored to individual patients.…”
Section: Pharmacology Of Antifibrinolytic Therapymentioning
confidence: 99%
“…As documented by both the streptokinase clot lysis time [29] and plasminogen activity assay [22], oral or intravenous (IV) EACA administration of 36 g per day produces a maximum steady state inhibition of fibrinolysis in 12-72 h [11,22,29,30]. Maximum inhibitory plasma concentration of TXA is reached within 12 h of IV administration of 1 g of the drug every 4 h without a loading dose [24,25].…”
Section: Pharmacology Of Antifibrinolytic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Takashima et al [81 showed that fibrinolytic activity in brain tissue obtained at autopsy was localised especially to the vascular endothelium. Newborn cerebral vascular endothelium showed less fibrinolytic activity than did adult brain, Following subarachnoid haemorrhage in adults, fibrinolytic activity on fibrin agar plates can be demonstrated in the CSF in some cases [4,9] but no data are available for infants with intracranial haemorrhage. Cross-linked FDPs in the CSF in preterm infants with IVH were raised and were even higher in those going on to develop hydrocephalus [11].…”
Section: Introductionmentioning
confidence: 94%